The effects of public procurement requirements and voluntary standards on environmental product innovation - Bastian Krieger; Anne Marie Rainville (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2025)
Public procurement requirements and voluntary standards are increasingly used to foster environmental product innovations. However, quantitative evidence on their individual and joint effects is absent, and their conceptualization remains at an early stage. This paper makes two contributions. First, it introduces the distinction between rigid threshold and flexible benchmark uses of voluntary standards in public tenders, theorizing their opposing effects on environmental product innovations. Second, using data from 5,127 firms in the 2021 German Innovation Survey and applying linear probability models, it provides the first quantitative analysis of their individual and joint effects across varying degrees of environmental significance. Results show that public procurement requirements and voluntary standards individually increase the probability of firms introducing environmental product innovations with high environmental significance. However, their interaction reveals a negative effect - discomplementarity - likely driven by rigid standard use, which offsets the effectiveness of procurement requirements. For environmental product innovations with low environmental significance, only voluntary standards exhibit a positive effect. These findings suggest that voluntary standards might limit the capacity of public procurement to foster more radical or disruptive environmental product innovations, while supporting more incremental innovations when used independently.
Keywords: O31; O38; Q55; Q58; 330; Public procurement; Voluntary standards; Environmental innovation